Experiences of newly qualified dentists in delivering oral health advice to parents/caregivers of young children—challenges and solutions - Rutter, Lucy; Duara, Raginie; Vinall-Collier, Karen A.; Owen, Jenny; Haley, Isabelle; Gray-Burrows, Kara A.; Hearnshaw, Simon; Marshman, Zoe; Day, Peter F. (Frontiers in Oral Health, 2023)
Introduction: A key skill for dental professionals to master is their ability to have effective preventive oral health conversations. On qualifying, UK dentists undertake a one-year foundation training programme in general practice. This study explored with Foundation Dentists, the barriers and facilitators to undertaking oral health conversations with parents/caregivers and their children, aged 0-11 years old. Materials and methods: Approximately 100 Foundation Dentists from the Yorkshire and Humber region attended a series of focus groups. They discussed how they and their wider dental team undertake oral health conversations with parents of young children, aged 0-11 years old. The data was analysed using thematic analysis. Results: Five themes were identified as barriers and facilitators to providing oral health advice: (1) Lack of knowledge around parenting skills and child development; (2) Parental receptivity; (3) Motivation for changing behaviours; (4) Information content and inconsistency; and (5) Current NHS structures of general dental practice. Discussion: A multi-faceted approach is needed to develop the training of Foundation Dentists to undertake preventive oral health conversations with parents and children. Such an approach has the potential to improve the patient-practitioner relationship and increase effective behaviour change conversations taking place in general dental care, thus improving children’s oral health.